Extraction and identification of amygdalin in seeds of some Syrian Rose's almonds (sweet almond, bitter almond and apricot) using reverse phase high-performance liquid chromatography (RP-HPLC). - محمود, حسن; جهينة ديب (Latakia University Journal -Basic Sciences Series, 2023)
In this research, amygdalin was extracted from the seeds of some roses almonds fruits (sweet almond, bitter almond and apricot) and determined by using reverse phase liquid chromatography (RP-HPLC) with ultraviolet detector (DAD) on column C18 and mobile phase (water: methanol 60:40 v/v). The extraction was accomplished by reflux soaking with two types of solvents (water and ethanol) and by heating for different periods of time and temperatures. The measurements were carried out after achieving the ideal conditions for chromatographic separations, which showed linear correlation r = 0.999 and limits of detection of LOD and LOQ for amygdalin (5.72 mg/l) and (19.07 mg/l), respectively, with recovery (100.17±1.68%), and relative deviation (1.45 - 0.12%). The results clarified that soaking for 100 min at the temperature (100ºC in distilled water and 78.5ºC in ethanol) gave the highest yield either with aqueous or alcoholic extracts in comparison with lower temperatures. The analysis results showed unexpectedly difference between amygdalin content of bitter almonds (3.044g/100g)) and bitter apricot kernels (3.924g/100g), while the content of sweet almonds was (1.144g/100g)) which is the least and this is expected because there is no clear bitter taste of amygdalin despite of its existence.